Diagnóstico situacional durante el primer semestre de la pandemia en el proceso de enseñanza-aprendizaje en preescolar. - Cadena, Gloria X. (2022)
When preparing this article, it was taken into consideration to identify the main strengths and threats presented in the teaching-learning process during the first semester of the pandemic in preschool education, where social interaction is essential for personal development. It was a challenge for the teacher to find strategies with the use of technological resources. The research carried out was based on a mixed approach (quantitative and qualitative), its respective inquiry was carried out on the population of the first year of basic education of the Cardenal Carlos María de la Torre Educational Unit, made up of five-year-old children, through the application of surveys designed for preschool teachers and parents. The information obtained reflects the effects caused in the teaching-learning process in preschool education during the pandemic and the importance of social interaction and coexistence with their peers. It also allowed to know the changes that occurred in the teaching-learning process in an education carried out through the use of different technological platforms, and the different challenges to which all those who were part of this educational process were subjected during the time of confinement: teachers, fathers, mothers and preschool students. It was necessary to create strategies for significant virtual learning through own experiences acquired from their reality. This article has been documented based on contributions received in relation to preschool education seen from the diversity of the COVID-19 pandemic and its effects.